Kedudukan Pejabat Pembuat Komitmen dalam Pengelolaan Keuangan Daerah di Kabupaten Sidoarjo - Made, Wahyu Herison (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2017)
The purpose of this study found and described the Position of Commitment Making Officials in Regional Financial Management in Sidoarjo Regency in accordance with applicable legal regulations. This type of research used legal research. The method used qualitative approach. The approach in this study used normative juridical approach. Source of data used secondary data. Data collection is done by conducting library studies (Library Research). The results of the study explained that Minister of Administrative Reform and Bureaucratic Reform Number 77 of 2012 concerning the Functional Position of Government Goods / Services Procurement Managers and Credit Figures and Joint Regulations of Head of LKPP and Head of State Civil Service Agency Number 1 of 2013 and Number 14 of 2013 had consequences law related to government procurement of goods / services. The regulation emphasized the requirements for the management of government goods / services, one of which was the Commitment Making Officer (PPK) was a Civil Servant (PNS) with a position as a career functional official who was included in the functional administrative clump.